Social weaknesses versus environmental conservation of Extractive Reserves in the Amazon - Freitas, Josimar; Florit, Luciano; Farias Filho, Milton; Homma, Alfredo (Caderno de Geografia, 2021)
Extractive Reserves (RESEXs) in the Amazon were created in order to improve the living conditions of its inhabitants and protect natural resources. Seeking to observe this reality, this study aimed to evaluate social and productive policies from the perspective of socio-environmental sustainability of two RESEXs from the Brazilian Amazon. Data and information were generated through observations, interviews and use of a questionnaire with 150 residents of 29 communities of the RESEXs Alto Juruá (Acre) and Rio Ouro Preto (Rondônia) located in the Brazilian Western Amazon. The results indicate the distance between social, economic and forest protection policies led the RESEXs to decline. The conclusion is that the sustainability of these areas depends on social policies associated with economic, ecological and partnership policies that value environmental resources and ensure the maintenance of the minimum living conditions of the inhabitants.